Computational fluid dynamics for the design of a novel bioreactor - Chai, Stanley Yee Zern (2010)
This project is intended to design a novel bioreactor that is able to simulate physiological human intestinal environment while performing clinical trials in it. The bioreactor will be able to assist researchers in monitoring and analyzing the performance of the drug and its uptake into the intestinal system. Simulations of the first few revisions of the bioreactor was performed on a computational fluid dynamic software named COMSOL and after review, was drawn into AutoCAD for fabrication. The result obtained from the final design that was simulated in COMSOL highly suggests that the design will be able to support low laminar flow rates which is most suitable for the seeding of Caco-2 cells.